Assessment of the cellulose-decomposing potential of soil biota near the railway tracks of the city of Karaganda - Dolgireva, V.; Belyaev , A.; Belyaev , I.; Amirkhanova , Zh; Drobchenko , Y. (Fundamental and Experimental Biology, 2025)
The aim of the study was to assess the cellulose-degrading potential of soil biota in the areas adjacent to the railway tracks of the city of Karaganda. Soil samples were collected along the railway line between the stations Vishnyaki and O.P. 721 km using the envelope method. Agarized Getchinson’s medium was used to isolate cellulose-degrading microorganisms. The total cellulolytic activity was evaluated by the level of acid formation in liquid Getchinson’s medium. A gradient of decreasing cellulolytic activity was observed from points 50 meters away from the railway to those at a distance of 10 meters. Regardless of soil composition, an increase in cellulose-degrading microorganisms was found at the points further from the railway. The change in total cellulose-degrading activity in the studied points was accompanied by a variation in the structure of autochthonous microbiota capable of cellulose decomposition. The findings highlight the need for further investigation of soils in areas adjacent to railway lines.